2018
DOI: 10.1038/s41379-018-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing of Xp11 translocation-associated cancers reveals novel gene fusions and distinctive clinicopathologic correlations

Abstract: Both Xp11 translocation renal cell carcinomas and the corresponding mesenchymal neoplasms are characterized by a variety of gene fusions involving TFE3. It has been known that tumors with different gene fusions may have different clinicopathologic features; however, further in-depth investigations of subtyping Xp11 translocation-associated cancers are needed in order to explore more meaningful clinicopathologic correlations. A total of 22 unusual cases of Xp11 translocation-associated cancers were selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
115
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(132 citation statements)
references
References 58 publications
5
115
3
1
Order By: Relevance
“…Cumulative studies have identified several gene fusion partners of TFE3 , including UBX domain containing tether for SLC2A4 ( ASPSCR1 ), proline‐rich mitotic checkpoint control factor ( PRCC ), and splicing factor proline and glutamine rich ( SFPQ ) . Less frequent fusion partners such as mediator complex subunit 15 ( MED15 ) and dishevelled segment polarity protein 2 ( DVL2 ) have also been identified . The histological diagnosis of Xp11 translocation RCCs is based on a characteristic morphology, such as papillary architecture composed of clear epithelioid cells with psammoma bodies, and strong nuclear immunostaining of TFE3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative studies have identified several gene fusion partners of TFE3 , including UBX domain containing tether for SLC2A4 ( ASPSCR1 ), proline‐rich mitotic checkpoint control factor ( PRCC ), and splicing factor proline and glutamine rich ( SFPQ ) . Less frequent fusion partners such as mediator complex subunit 15 ( MED15 ) and dishevelled segment polarity protein 2 ( DVL2 ) have also been identified . The histological diagnosis of Xp11 translocation RCCs is based on a characteristic morphology, such as papillary architecture composed of clear epithelioid cells with psammoma bodies, and strong nuclear immunostaining of TFE3.…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8 Less frequent fusion partners such as mediator complex subunit 15 (MED15) and dishevelled segment polarity protein 2 (DVL2) have also been identified. [8][9][10] The histological diagnosis of Xp11 translocation RCCs is based on a characteristic morphology, such as papillary architecture composed of clear epithelioid cells with psammoma bodies, and strong nuclear immunostaining of TFE3. Nuclear TFE3 immunoreactivity is highly sensitive and specific for diagnosing Xp11 translocation RCC 11 ; however, suboptimal fixation or high endogenous TFE3 expression may result in equivocal immunostaining.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical stains for TFE3, TFEB, cathepsin‐K, and MITF are often positive in these tumors, although the specificity and sensitivity of these analytes for tRCC's are far from perfect. Prolonged fixation time, presence of necrosis, antibody specificity, variation in technical methods, and scoring systems are sources of error—leading to both false positive and false negative results . Morphologic and immunohistochemical findings can prompt reflex fluorescence in situ hybridization (FISH) with break‐apart probes that are currently considered a gold standard in diagnosing tRCC .…”
Section: Introductionmentioning
confidence: 99%
“…However, break‐apart FISH analysis has significant limitations, such as fixation and cutting artifacts, borderline results due to low‐frequency split signals—especially for inversions/intrachromosomal fusions, interpretation subjectivity, and an inability to detect precise breakpoints, cryptic fusions or partner genes in rearrangements . Likewise, RT‐PCR and cytogenetic studies have numerous drawbacks and challenges in routine diagnostic application often requiring higher quality fresh‐frozen specimens for adequate results, A study by Wang et al showed no failed samples by RNA‐seq method vs a 41% failure rate of RT‐PCR followed by Sanger sequencing in the same set of cases. Moreover, RT‐PCR can only identify known fusion with known breakpoints, which is a major limitation as the spectrum of new fusion partners and diverse breakpoints constantly expands causing false negative results …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation